2013 International Conference on Energy Efficient Technologies for Sustainability 2013
DOI: 10.1109/iceets.2013.6533388
|View full text |Cite
|
Sign up to set email alerts
|

A parametric study on the improvement of pressure recovery coefficient of a conical diffuser using Computational Fluid Dynamics

Abstract: The easiest and most practical way to make any system more environmentally friendly is to increase its energy efficiency. In a commercial gas turbine, this is done by attaching a diffuser at the turbine exit. The purpose of this study is to determine the combination of flow parameters and the diffuser design that would lead to the improvement of the pressure recovery coefficient of such a conical diffuser, and hence the overall efficiency of the turbo machine, like an industrial gas turbine, to which the diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The transparent extension piece (55 mm inner diameter with a 24 mm diameter annular insert) provides access for the hot-wire anemometry (HWA) probe and a thermocouple used for measurement of the axial and tangential velocity components across the annulus. A sudden expansion diffuser (6) connects the swirl generator assembly to the monolith (7) of diameter, 𝐷 = 145.8 mm, followed by an outlet sleeve (8).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transparent extension piece (55 mm inner diameter with a 24 mm diameter annular insert) provides access for the hot-wire anemometry (HWA) probe and a thermocouple used for measurement of the axial and tangential velocity components across the annulus. A sudden expansion diffuser (6) connects the swirl generator assembly to the monolith (7) of diameter, 𝐷 = 145.8 mm, followed by an outlet sleeve (8).…”
Section: Methodsmentioning
confidence: 99%
“…For wide-angle open diffusers, Okhio et al [5] have shown that increasing swirl number can suppress separationclearly of benefit for catalyst assemblies. However, high swirl can lead to the development of very low pressures in the centre of the vortex leading to flow reversal accompanied by a strong recirculating zone within the diffuser and additional pressure loss [5]- [8]. Very few studies exist of the effect of the downstream conditions on the flow structure.…”
Section: Introductionmentioning
confidence: 99%